Vibration fatigue dynamic stress simulation under non-stationary state. (1st January 2021) - Li, Fansong; Wu, Hao; Wu, Pingbo
Highlights: The formula of window bandwidth in determining non-stationarity factor is derived. Convert mode superposition method into time domain to solve non-stationary process. The influence of modal parameters on non-stationary stress and damage is analyzed. Abstract: The methods of vibration fatigue stress simulation and strength evaluation under stationary state are quite complete, but the research on vibration fatigue under non-stationary state is insufficient. Based on the theory of structural dynamics and the principle of modal superposition method, the formula for calculating the dynamic stress of vibration fatigue under non-stationary state is deduced in this paper. The complex frequency response function (FRF) of each mode is calculated by finite element program, and the impulse response function (IRF) of each mode is obtained by inverse fast Fourier transform (IFFT) method, so as to realize the decoupling of each mode. Then the principle of modal superposition method is applied to time domain, considering the external multi-input loads of the structure, the dynamic stress caused by each external load can be obtained by convolution calculation based on the load and the corresponding IRF. The final dynamic stress can be obtained by superposition of the dynamic stress caused by each load. So, this method can easily calculate the effect of each mode or each external load on structural damage, which is helpful for the study of structural vibration fatigue failure reasons. Finally, the simulated dynamic stress under non-stationary state is compared with the experimental dynamic stress, and three indicators, which are average maximum stress, structural damage and frequency evolution, are taken into account in the comparison. Compared with the experimental data, the damage error calculated by the stress time history between simulation and experiment is 2.84%, the trend of stress time history obtained by simulation is almost the same as the experimental result, and the frequency evolution process under non-stationary state can also be reproduced well. The comparison results show that the proposed method in this paper can be used as an effective reference for structural vibration fatigue dynamic stress simulation under non-stationary state.